Calcium signals in guard cells enhance the efficiency by which abscisic acid triggers stomatal closure. Issue 1 (19th July 2019) - Huang, Shouguang; Waadt, Rainer; Nuhkat, Maris; Kollist, Hannes; Hedrich, Rainer; Roelfsema, M. Rob G.
Summary: During drought, abscisic acid (ABA) induces closure of stomata via a signaling pathway that involves the calcium (Ca 2+ )‐independent protein kinase OST1, as well as Ca 2+ ‐dependent protein kinases. However, the interconnection between OST1 and Ca 2+ signaling in ABA‐induced stomatal closure has not been fully resolved. ABA‐induced Ca 2+ signals were monitored in intact Arabidopsis leaves, which express the ratiometric Ca 2+ reporter R‐GECO1‐mTurquoise and the Ca 2+ ‐dependent activation of S‐type anion channels was recorded with intracellular double‐barreled microelectrodes. ABA triggered Ca 2+ signals that occurred during the initiation period, as well as in the acceleration phase of stomatal closure. However, a subset of stomata closed in the absence of Ca 2+ signals. On average, stomata closed faster if Ca 2+ signals were elicited during the ABA response. Loss of OST1 prevented ABA‐induced stomatal closure and repressed Ca 2+ signals, whereas elevation of the cytosolic Ca 2+ concentration caused a rapid activation of SLAC1 and SLAH3 anion channels. Our data show that the majority of Ca 2+ signals are evoked during the acceleration phase of stomatal closure, which is initiated by OST1. These Ca 2+ signals are likely to activate Ca 2+ ‐dependent protein kinases, which enhance the activity of S‐type anion channels and boost stomatal closure.